2020
DOI: 10.1111/gfs.12497
|View full text |Cite
|
Sign up to set email alerts
|

Pasture production, persistence of legumes and lamb growth in summer‐dry hill pastures

Abstract: Nitrogen (N) is a pivotal element that drives plant growth, yet it is the most limiting nutrient for pasture production (Mills, Moot, & Jamieson, 2009). In particular, dryland pasture soils in arid and temperate regions are often low in N. Therefore, increasing N availability in dryland pastures that are managed under low-input production systems is a primary need to improve productivity. Application of chemical fertilizers can be costly and challenging, particularly in difficult terrains such as hill and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The lamb growth rates in the current study was similar to those reported by Warner and Sharrow (1984) for spring (73-165 g head −1 d −1 ) and early summer (−13-98 g head −1 d −1 ) periods in a 3 year-grazing study. In contrast, Gultekin et al (2020) reported greater lamb liveweight gains in dryland hill pastures in Pacific Northwest where the lamb growth rates were maintained over 141 g head −1 d −1 in the late spring season (May-June). It is of note that the newly established pastures reported in Gultekin et al (2020) study contained over 20% legume indicating the value of high legume content of pastures for improved forage quality and high lamb growth rates particularly in dryland pastures (Hyslop et al, 2000;Mills et al, 2015).…”
Section: Lamb Production Did Not Differ Despite Lower Herbage On Offer In Solar Pasturesmentioning
confidence: 76%
“…The lamb growth rates in the current study was similar to those reported by Warner and Sharrow (1984) for spring (73-165 g head −1 d −1 ) and early summer (−13-98 g head −1 d −1 ) periods in a 3 year-grazing study. In contrast, Gultekin et al (2020) reported greater lamb liveweight gains in dryland hill pastures in Pacific Northwest where the lamb growth rates were maintained over 141 g head −1 d −1 in the late spring season (May-June). It is of note that the newly established pastures reported in Gultekin et al (2020) study contained over 20% legume indicating the value of high legume content of pastures for improved forage quality and high lamb growth rates particularly in dryland pastures (Hyslop et al, 2000;Mills et al, 2015).…”
Section: Lamb Production Did Not Differ Despite Lower Herbage On Offer In Solar Pasturesmentioning
confidence: 76%
“…In a recent special-theme issue of GFS on annual and perennial forage legumes in dryland pasture systems , the role of legumes was addressed in a systems context. Breeding, species choice and regional adaptation (e.g., Bekuma et al, 2021), the development of novel agronomic practices (Harrison et al, 2021) through to animal production and grazing management were addressed (e.g., Gultekin et al, 2021;Norman et al, 2021). Nutt et al (2021) reported on the evaluation of "summer sowing", an innovative approach to increase the adoption of recently domesticated species of hard-seeded annual legumes in Mediterranean and temperate climate zones.…”
Section: Adaptation To Harsher Climatesmentioning
confidence: 99%
“…In a recent special‐theme issue of GFS on annual and perennial forage legumes in dryland pasture systems (Smith & Elgersma, 2021), the role of legumes was addressed in a systems context. Breeding, species choice and regional adaptation (e.g., Bekuma et al, 2021), the development of novel agronomic practices (Harrison et al, 2021) through to animal production and grazing management were addressed (e.g., Gultekin et al, 2021; Norman et al, 2021).…”
Section: Adaptation To Harsher Climatesmentioning
confidence: 99%
“…In these cases, the introduction of Al-tolerant species could improve the production of forage biomass and profit while minimizing financial costs. The total annual yields of pastures that contain a greater proportion of legumes are generally higher than grass monocultures (Gultekin et al, 2021). Lotus species are recognized for their tolerance to acid soils and low natural soil fertility (Escaray et al, 2012), and in South America, legumes are currently being more widely adopted as an alternative to improve the quality and quantity of pasture in regions with acid soils (Kapp-Bitter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%